Teknik Sinematografi Praktis Menggunakan Smartphone bagi Dosen Pengabdi di Lingkungan Universitas Negeri Makassar - Baso Indra Wijaya Aziz (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Experiences from the fields of science cultivated by lecturers can be poured into teaching materials, textbooks, reference books, research materials, study materials, and the like that are full of benefits. The benefit of this training is to help the devoted lecturers in making compulsory outcomes from community service activities in the form of making videos. Video making material in the form of a collection of photos and videos that are owned so that it will become a digital archive that can be enjoyed by everyone. For this reason, cinematographic basic techniques are needed as a basic principle so that lecturers can process their photos and videos so they can talk a lot in accordance with the desired motivation. The steps are in the form of (1) smartphone settings (2) picture taking technique (3) narration making (4) editing technique (5) uploading to YouTube social media. Through the implementation of the Community Partnership Program it can be seen that the interest and enthusiasm of lecturers in Makassar State University is very high to learn and maximize the functions and features of smartphones, basic techniques for taking good pictures, how to process and edit video with a smartphone, to feel First experience of uploading videos to YouTube social media.